THE EXISTENCE OF CRIMINAL LAW IN NATIONAL CRIMINAL LAW REFORM - Abdul Kholiq; Zabidin Zabidin; Pratiwi Ayu Sri Daulat (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
The problem of reforming criminal law is one of the impo important issues that need in all its aspects in connection with efforts to reform criminal law in our country. It is said to be important and even the most important because legal experts often interpret criminal law as a double-edged sword. On the one hand, it is a law to protect society from the threat of crime, but on the other hand, there are times, there are times when human rights temporarily or permanently deprive a person of liberty. Criminal law reform has existed since 1946 with the issuance of Law Number 1 of 1946 concerning criminal law regulations. Criminal law reform as part of criminal politics is in place, and it is time to implement it. This is mainly related to the provisions of the old criminal law, which are regulated in the criminal law code as an "umbrella act" or an umbrella law of a general nature. This law will also affect the formulation of special criminal laws, following the legal needs of society in this era of independence and openness in the 21st century. Based on the description of the background, the formulation of the problem that will be presented is as follows: Why is the renewal of the national criminal law important? How is the formation of criminal law reform in the national Criminal Code Bill? Based on these problems, the discussion is as follows: The existence of the new Criminal Code has become important which is sourced, characterized, rooted, and has a national character following the contents of Pancasila and the 1945 Constitution, is now very urgent to be realized to replace the old Criminal Code which is a legacy of the Dutch colonial and is no longer compatible with developments. Social, cultural, economic, political, and technological conditions in an atmosphere of independent Indonesia and only undergoing reform in the 21st century. The establishment of the new Criminal Code is a reflection of the government's serious efforts in enforcing criminal laws that are more humane and fair for all levels of society in this reform era. . It would be strange if the Netherlands, WvS had long been revised and not enforced, would continue to apply as a colonial legacy, because of the inability of this nation to create a new national criminal law.